In the Eye of the Storm: Entrepreneurs and Well-Being During the COVID-19 Crisis. (May 2023) - Backman, Mikaela; Hagen, Johannes; Kekezi, Orsa; Naldi, Lucia; Wallin, Tina
In this paper, we examine the impact of the COVID-19 pandemic on the well-being of entrepreneurs. We surveyed a representative sample of Swedish entrepreneurs and wage employees at different stages of the COVID-19 pandemic. The survey data, combined with register data, show that the COVID-19 outbreak has a negative effect on the well-being of entrepreneurs in terms of increased perceived stress. However, this negative effect is weaker for entrepreneurs who feel younger than their chronological age and entrepreneurs who are geographically distant from the epicenter of the crisis.